HOW TO USE SOURCES IN ACADEMIC WRITING - Irina B. Korotkina (Высшее образование в России)
The author considers key issues concerning quoting, referencing and using sources in academic writing faced by Russian students and specialists when dealing with international requirements of Western universities and publishers.